Breastfeeding Pattern and its Associated Factors Among Mothers Working at Two Hospitals in Kathmandu - Basnet, Srijana; Shrestha, Merina; Adhikari, Tulashi; Shakya, Aarati (Journal of Nepal Paediatric Society, 2020)
Introduction: Breastfeeding practices of women working at the hospital are likely to be modified by the facilities and support that they receive at the hospital. This study was done to evaluate the breast feeding practices and to analyse important factors that are associated with exclusive breast feeding till six months among women working at hospitals in Kathmandu, Nepal Methods: A total of 110 women, with a young child between the ages of six months and two years were recruited from two hospitals in Kathmandu. A predesigned structured, interviewer-administered questionnaire was used for data collection. Results: The mean age of the mothers was 29.85 ± 3.68 years. Ninety seven (88.2%) women were aware about initiation of breastfeeding within first hour of birth but only 64 (58.2%) women could practice it. Most women 100 (90.9%) were aware about exclusive breastfeeding but only 18 (16.3%) could practice exclusive breastfeeding till six months. Mean duration of exclusive breastfeeding was 2.86 ± 2.00 months and 20 (18.2%) mothers practiced mixed feeding since birth. The participants whose babies had prelacteal feeding had significantly shorter duration of mean exclusive breast feed 1.92 ± 2.18 (S.D) compared to those who did not have prelacteal feed 3.33 ± 1.74 (S.D) (p = 0.001). Those who delivered by normal vaginal delivery, initiated breastfeeding within first hour of delivery, expressed breast milk and got feeding breaks were associated with longer duration of mean exclusive breast feed. Conclusion: The breast feeding practices among working women at hospital is quite low compared to national statistics on IYCF. Breast milk expression and feeding breaks for lactating working women could improve feeding practices.